MA'HAD 'ALY AND ISLAMIC HIGHER EDUCATION IN CONTEMPORARY INDONESIA: Contributions, Dynamics of Intellectualization, and Scientific Independence of Islamic Boarding Schools - Niam, Khoirun; Hamid, Abdulloh; Candra Yudha, Ana Toni Roby; Sulaeman, Mubaidi (JOURNAL OF INDONESIAN ISLAM, 2025)
This study examines the role of Ma’had Aly and Private Islamic Higher Education Institutions (PTKIS) managed by pesantren in Indonesia in strengthening the scientific independence of Islamic boarding schools through intellectualization. The research is based on field observations and interviews conducted at 12 pesantren offering Ma’had Aly and postgraduate programs, analyzed using Creswell’s analytical approach. The findings indicate that Ma’had Aly and PTKIS postgraduate programs significantly enhance the intellectual capacity of santri, not only in mastering Islamic religious sciences but also in developing related disciplines such as social and natural sciences. These programs encourage the integration of traditional pesantren learning with formal higher education, introducing more advanced and systematic intellectual frameworks within Islamic studies. Furthermore, they provide opportunities for santri to cultivate critical thinking, apply scientific methodologies, and engage in interdisciplinary research. The study concludes that integrating Islamic higher education into pesantren enriches Islamic educational theory and demonstrates the continuing relevance of pesantren in responding to modernization and globalization.